Contested commons: Agricultural modernization, tenure ambiguities and intra-familial land grabbing in Ghana. (June 2018) - Kansanga, Moses; Andersen, Peter; Atuoye, Kilian; Mason-Renton, Sarah
Highlights: Agricultural modernization is intensifying land use conflicts at the family level. Competition over family land has opened up the customary land tenure system to multiple interpretations. Intra-familial land grabbing which we conceptualize as ' intimate dispossession ' is prevalent. Smallholder farmers are adopting personal tenure protection strategies to resist ' intimate dispossession '. Abstract: Agricultural land in northern Ghana is a common pool resource predominantly governed by longstanding customary land tenure provisions. Following the renewed emphasis at achieving a new green revolution for Africa since the last decade, the government of Ghana has prioritized the provision of improved land preparation technologies to smallholder farmers. Although the uptake of these technologies has introduced speed and efficiency in land preparation, there are concerns about the impacts on customary land tenure systems. Drawing on the experiences of smallholder farmers (n = 60) in northern Ghana using in-depth interviews, we examine the dynamics in contemporary agricultural land access and governance following decades of progressive agricultural modernization. Our findings show that agricultural modernization has intensified agricultural land use and exposed the customary land governance system to more rival claims over agricultural commons that were previously owned and cultivated collectively under the extended family system. Given the current ambiguities in the interpretation of customary tenure and concomitant intra-familial land grabbing among smallholder farmers which we term ' intimate dispossession ', most farmers have resorted to diverse personal tenure protection strategies towards enhancing their land use rights at the expense of co-family members. We advocate a land reform that prioritizes formal registration of agricultural lands to avoid future ambiguities in ownership and a cycle of farmland take-overs. With increasing pressure from other competing land uses, land banking should be prioritized to ensure tenure security for smallholder farmers, particularly weaker social groups and individuals within families who are often at risk of intra-familial land grabbing.